Competitiveness of Russia ; problems and perspectives - Kuzin, Dimitry V. (Pecvnia : Revista de la Facultad de Ciencias Económicas y Empresariales, Universidad de León, 2007)
This paper reviews general contemporary issues of competitiveness of Russia on a global stage and suggests some possible scenarios of further development which could improve the world ratings of Russia. After a brief introduction devoted to modern concepts of national competitiveness, the author analyse current competitive positioning of Russia using the results of the world’s most influential research reports and rankings. This part of the paper reveals the most serious indicators of Russia’s lag behind the leading and other similar in size, as well as potential and development stage countries.The next three parts of the paper analyze both positive and negative trends of recent Russia’s development over the last 6 years as it is viewed from Russian expert’ point of view. The essence of the current debate on the future of the country, after the next Presidential election, is also presented with emphasis on several feasible strategies and their potential influence on the future competitiveness of the country. At the end the paper addresses the issue of values modernization in Russia which seems to be crucial not just to improve competitiveness but to ensure the future development of the country.The views and estimates expressed in the paper except for references to different expert opinions are the authors own responsibility and should not be interpreted as presenting an official position on these issues. El presente trabajo hace una revisión general de los aspectos contemporáneos de la capacidad competitiva de Rusia a nivel global e indica posibles situaciones para un desarrollo que pueda mejorar la valoración mundial de Rusia. Tras una breve introducción, dedicada a conceptos modernos de competitividad nacional, el autor analiza la situación competitiva actual de Rusia utilizando los resultados de los informes y clasificaciones más influyentes a nivel mundial. Esta sección del artículo facilita los indicadores más rigurosos de la posición de Rusia en relación con países similares así como sus posibilidades de desarrollo.Las tres partes siguientes del trabajo analizan las tendencias positivas y negativas del desarrollo de Rusia durante los seis últimos años. También se presenta la esencia del debate actual sobre el futuro del país, una vez que se celebre la próxima elección presidencial, prestando especial atención a varias estrategias posibles y su influencia potencial en la competitividad del país en el futuro. Al final del trabajo se aborda el aspecto de la modernización de valores en Rusia, lo que parece ser fundamental no sólo para mejorar la competitividad sino también para asegurar el desarrollo venidero del país. Las consideraciones que se expresan en el artículo, salvo aquéllas que específicamente se referencian, corresponden al autor y no deben interpretarse como oficiales.